The sponge Oscarella lobularis (Porifera, Homoscleromorpha) as a suitable biomonitor of metallic contamination in Mediterranean coastal ecosystems. (March 2023) - de Pao Mendonca, Kassandra; Angeletti, Bernard; Dufour, Aurélie; Borchiellini, Carole; Heimbürger-Boavida, Lars-Eric; Renard, Emmanuelle; Issartel, Julien
Abstract: The biomonitoring of metallic contamination in marine ecosystems is often focused on animal species of commercial interest and in lesser extent on non-model marine invertebrates. The aim of this study was to compare the metal concentrations (Li, Al, Ti, Cr, Fe, Ni, Cu, Zn, As, Ag, Cd, Hg, Pb) in seven marine sponges with a particular interest in the homoscleromorph sponge Oscarella lobularis at different sites of the Bay of Marseille, France. Inter-species variabilities suggest that the seven sponge species studied accumulate metals differently. In O. lobularis, a multi-site analysis shows different bioaccumulation between the eight sampled populations. These inter-site differences may reflect differences in the hydrodynamic features and in past and present industrial activities. Because Oscarella lobularis shows a homogeneous metal accumulation pattern in comparison with the other tested species, it appears to be suitable for metal contamination biomonitoring in Mediterranean coastal waters, in particular of the coralligenous communities. Graphical abstract: Unlabelled Image Highlights: The sponge Oscarella lobularis shows site-dependent metal concentrations. Metals are differently accumulated between sponge species at the same site. O. lobularis can be a suitable bioindicator of metallic contamination of coastal waters.